5'-Phosphonate modified oligoadenylates as potent activators of human RNase L - Lášek, Tomáš; Petrová, Magdalena; Košiová, Ivana; Šimák, Ondřej; Buděšínský, Miloš; Kozák, Jaroslav; Snášel, Jan; Vavřina, Zdeněk; Birkuš, Gabriel; Rosenberg, Ivan; Páv, Ondřej (Bioorganic & medicinal chemistry, 2022)
The oligoadenylate synthetase-ribonuclease L pathway is a major player in the interferon-induced antiviral defense mechanism of cells. Upon sensing viral dsRNA, 5'-phosphorylated 2',5'-oligoadenylates are synthesized, and subsequently activate latent RNase L. To determine the influence of 5'-phosphate end on the activation of human RNase L, four sets of 5'-phosphonate modified oligoadenylates were prepared on solid-phase. The ability of these 5'-modified oligoadenylates bearing shortened, isosteric and prolonged phosphonate linkages to activate RNase L was explored. We found that isosteric linkages and linkages prolonged by one atom were in general well tolerated by the enzyme with the EC50 values comparable to that of the natural activator. In contrast, linkages shortened by one atom or prolonged by two atoms exhibited decrease in the activity.
Keywords: Endoribonucleases; Structure-Activity Relationship; Adenine Nucleotides; vztah mezi dávkou a účinkem léčiva; konformace nukleové kyseliny; vztahy mezi strukturou a aktivitou; Dose-Response Relationship, Drug; Humans; Organophosphonates; Nucleic Acid Conformation; endoribonukleasy; oligoribonukleotidy; Oligoribonucleotides; organofosfonáty; lidé; adeninnukleotidy